Pendidikan Hukum Lalu Lintas bagi Pengendara Muda di SMA Muhammadiyah Kota Jayapura: Pengabdian - Ika Fitrianita; Muhamad Sofian; M. Khaidir Kahfi Natsir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The main objective of this community service activity is to improve the understanding and awareness of traffic law for young drivers of SMA Muhammadiyah Jayapura City students. The research method uses a descriptive qualitative method with stages from interviews, observations, and literature studies. The results of the study indicate that socialization through Traffic Law Education for Young Drivers at SMA Muhammadiyah Jayapura City is effective in improving understanding and awareness of traffic law. In addition, the involvement of law enforcers who simulate the legal process is one of the factors that facilitate students' understanding of the law. The influence of the social environment, such as peers, often encourages disobedient behavior, especially traffic laws. There is a very close correlative relationship between social behavior and law. Therefore, efforts are needed to increase legal awareness for young drivers which can be done with two alternatives, namely by implementing Counseling and Legal Education about the dangers of traffic violations for SMA Muhammadiyah Jayapura City students and partnering with law enforcement officers. Increasing awareness and understanding of traffic law is expected